A Municipalização do verde público na cidade de São Paulo: Da administração dos jardins públicos e arborização (1900) à subdivisão de parques, jardins e cemitérios (1935) - Bartalini, Vladimir (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2001)
This article deals with the provision of recreational green areas in the municipal administration area of São Paulo. This study of public provision deals with a period which begins with the setting up of the Agency of Public Gardens, in 1893, and ends with the creation of the Subdivision of Parks, Gardens and Cemeteries, in 1935. The article admits the important role of Antonio Etzel as the head of the agency responsible for public garden administration from 1900 up to 1930, when he retired. Qualifying the agencies difficulties, the article mentions the ways in which decisions concerning design and planning of the most important recreational green areas often escaped the control of this agency. Three main topics were analysed with the aim of describing the performance of the municipal administration in this sector: the organization of the municipal administration and the professional staff; the recreation habits of the population using green areas and the provision record of green areas as created and maintained by the municipality